Examining musical elements in Toy Story soundtrack “You’ve Got a Friend in Me” - Berehme Adyatma Purba; Raditya Alifamughni (Interlude: Indonesian Journal of Music Research, Development, and Technology, 2023)
Animated comedy and adventure films are highly enjoyable to watch. In addition to being an enjoyable film, it is also suitable for viewers of all ages, ranging from children to adults. Furthermore, films of this genre are often sought after by families seeking weekend entertainment. In addition to being captivating to watch, films in this genre typically aim to impart a moral message. The "Toy Story" is a well-known animated comedy about friendship and adventure. It effectively conveys a message of friendship, a familiar theme to viewers. The film's soundtrack, "You've Got a Friend in Me", is highly memorable and strongly associated with the movie. This essay will examine the audio of this renowned film. In this study, we employed qualitative methodologies. Qualitative methods refer to research approaches that aim to comprehend phenomena in a research object by describing them using language. This study aims to analyze the musical composition of the film "Toy Story" theme song to understand its characteristics and elements comprehensively. Data collection was conducted through discography investigations, book reviews, and observations. Discographic study involves analyzing, describing, and explaining the results of auditory experiences. We examined the "Toy Story" theme song in audio format, accessible on platforms like Spotify and YouTube, and the musical score. The purpose was to facilitate the evaluation of the song's form, structure, and musical elements. "You've Got a Friend in Me" exhibits a higher level of complexity in terms of chords and melody than a usual song. It surpasses the average in chord complexity, melodic complexity, chord melodic tension, chord progression novelty, and chord-bass melodies.